2009
DOI: 10.1021/jp810757x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Vibrational Coherences in Resonance Energy Transfer along MEH-PPV Chains at Room Temperature

Abstract: In this work we report a study of the role of coherence dynamics in the intermediate coupling regime of electronic energy transfer (EET). Starting from the idea that in the intermediate coupling regime the phase information should be partially retained in a transfer process from a donor to an acceptor, we designed a new ultrafast experiment based on anisotropy decay along two time axes, capable of probing the degree of coherence characterizing this transfer. Conjugated polymer (poly[2-methoxy-5-(2'-ethyl-hexox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
137
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(138 citation statements)
references
References 223 publications
1
137
0
Order By: Relevance
“…6,7,48 We will show in an upcoming paper 49 that this unusually high PL quenching of thick P3HT films by thin PCBM overlayers results from a novel long-range exciton quenching mechanism. 50,51 The green triangles in Figure 5 show that upon thermal annealing, the PL intensity from P3HT/PCBM bilayers undergoes a slight increase, indicating a decrease in exciton quenching efficiency. This result is in direct contrast to the work of Drees et al, who observed that thermal annealing led to increased quenching of the PL from interdiffused blends of a poly(phenylene vinylene) derivative and C 60 .…”
Section: Resultsmentioning
confidence: 99%
“…6,7,48 We will show in an upcoming paper 49 that this unusually high PL quenching of thick P3HT films by thin PCBM overlayers results from a novel long-range exciton quenching mechanism. 50,51 The green triangles in Figure 5 show that upon thermal annealing, the PL intensity from P3HT/PCBM bilayers undergoes a slight increase, indicating a decrease in exciton quenching efficiency. This result is in direct contrast to the work of Drees et al, who observed that thermal annealing led to increased quenching of the PL from interdiffused blends of a poly(phenylene vinylene) derivative and C 60 .…”
Section: Resultsmentioning
confidence: 99%
“…Transient anisotropy decay directly probes the orientational dynamics of transition dipole moments in a system consisting of multiple chromophores and has been used in the analysis of the lifetimes of coherent energy transfer and associated quantum coherence [70][71][72][73][74][75][76]. Following Ref.…”
Section: F Anisotropy Decaymentioning
confidence: 99%
“…In related areas of quantum transport, the intersite coherence was found to be of fundamental importance in electronic energy transfer in light harvesting complexes 28 and conjugated polymers. 29,30 It would be interesting if the intersite coherence can also be measured experimentally for charge carrier transport in organic materials.…”
Section: ͑8͒mentioning
confidence: 99%
“…Both the coherent and thermal assisted transport mechanisms are characterized within a unified theory, and the intersite coherence is found to have important implications for the charge carrier transport mechanism. The new method could also find wide applications in areas such as charge transport in DNA, 31 and exciton dynamics in conjugated polymers, 29,30 as well as many other problems mentioned in the introduction. …”
Section: ͑8͒mentioning
confidence: 99%